RESEARCH: "Individual Differences in the Theological Concept of God" - Trimeche, Samir (The international journal for the psychology of religion, 2006)
This study (a) examined the way in which omnipotence, omnipresence, omniscience, and eternity attributes were combined in people's minds to define God and (b) uncovered the various concepts of God different people could have in relation to these attributes and in various combinations of them. The technique that we used was borrowed from judgment and decision making and was especially suited for highlighting individual differences. The participants were 277 persons living in France, ages 15 to 50. They were presented with a series of vignettes that described a deity currently revered by the members of a supposedly recently studied tribe. The four main attributes used in each description were the omnipotence, omniscience, omnipresence, and eternity of the deity at hand. They were asked to rate each deity from the standpoint of its divine character. No less than six different theological concepts of God were found. For about 16% of the sample, God was essentially conceived as an omnipotent entity. For 38% of the sample, divine character was conceived as an additive function of omnipotence, omniscience, omnipresence, and eternity. For 14% of the sample, the concept of God conformed to the Judaic and Christian traditions. Divine character was conceived as a clearly all-or-nothing matter. A deity that did not possess all of the four previously mentioned attributes together could not be considered God. Finally, one group of participants, formed mainly of nonbelieving females, allowed the tribal peoples to make whatever they liked into God.